Time from symptoms onset to remdesivir is associated with the risk of ICU admission: a multicentric analyses - Rodrigo Alonso-Navarro; Margarita Ramírez; Mar Masiá; Roger Paredes; Rocío Montejano; Marina Povar-Echeverria; Jordi Carratalà; Miguel Salavert; Enrique Bernal; Carlos Dueñas; Juan Flores; Francisco Fanjul; et al. (BMC Infectious Diseases, 2023)
Abstract Background Shorter duration of symptoms before remdesivir has been associated with better outcomes. Our goal was to evaluate variables associated with the need of ICU admission in a cohort of hospitalized patients for COVID-19 under remdesivir including the period from symptoms onset to remdesivir. Methods We conducted a retrospective multicentric study analysing all patients admitted with COVID-19 in 9 Spanish hospitals who received treatment with remdesivir in October 2020. The main outcome was the need of ICU admission after 24 h of the first dose of remdesivir. Results In our cohort of 497 patients, the median of days from symptom onset to remdesivir was 5 days, and 70 of them (14.1%) were later admitted into ICU. The clinical outcomes associated with ICU admission were days from symptoms onset (5 vs. 6; p = 0.023), clinical signs of severe disease (respiratory rate, neutrophil count, ferritin levels and very-high mortality rate in SEIMC-Score) and the use of corticosteroids and anti-inflammatory drugs before ICU. The only variable significatively associated with risk reduction in the Cox-regression analyses was ≤ 5 days from symptoms onset to RDV (HR: 0.54, CI95%: 0.31–0.92; p = 0.024). Conclusion For patients admitted to the hospital with COVID-19, the prescription of remdesivir within 5 days from symptoms onset diminishes the need of ICU admission.